Answer:
y = x*(6 feet/1 fathom)
Explanation:
We know the relation:
1 fathom = 6 feet.
We can write:
1 = (6 feet/1 fathom)
Now, remember that any number multiplied by 1 does not change.
Then suppose that we have a measure of 3 fathoms, then:
3 fathoms = (3 fathoms)*1
= (3 fathoms)*((6 feet/1 fathom)) = (3 fathoms/1 fathom)*(6feet)
= 3*(6 feet) = 18 feet.
So we changed the units by multiplying the original measure by (6 feet/1 fathom)
Then, if x is the depth of water in fathoms and y is the depth of the water in feet, we can write:
y = x*(6 feet/1 fathom)